Respiration as Exercise Limiting Factor
Limitation of maximal exercise is generally explained by cardiovascular or neuromuscular factors. In healthy subjects, the respiratory system is not considered as an exercise limiting factor. In highly trained athletes oxygen diffusion limitations may occur but the respiratory pump should have enough reserve because even sedentary subjects are able to hyperventilate during heavy exercise. In daily life and during many athletic events, the ability to sustain a given percentage of VO2max for a period of time (endurance) is more relevant than VO2max itself. During this constant work exercise the respiratory system can become a limiting factor: We found that isolated training of the respiratory muscles (isocapnic hyperpnea during 4 weeks, 5 times per week 30 min) significantly increased the time to exhaustion at an exercise level between 64 and 85% VO2max. This improvement was 50% in sedentary and 30% in physically active subjects. The respiratory training significantly increased respiratory endurance and maximal voluntary ventilation but it did not affect the anaerobic threshold and VO2max. In contrast to physical endurance training, respiratory muscle training did not increase cardiac stroke volume. Also the decrease in blood lactate concentration during exercise after respiratory training, when compared to pre-training, can not explain the prolongation of cycling performance after respiratory training. We speculate that the increase in exercise endurance is a result of an increased fatigue resistance of respiratory muscles. It is known that respiratory muscle fatigue causes rapid shallow breathing which could lead to exhaustion. Towards the end of heavy exercise at a constant workload, minute ventilation typically increases and subjects become short of breath. This final increase of minute ventilation is due to a rise in breathing frequency. After respiratory training, respiratory muscles may be more fatigue-resistant and the increase in breathing frequency is delayed or absent. In addition to healthy persons, also patients will benefit from our research. E. Furrer-Boschung and Dr. W. Bauer at the Lindenhofspital, Bern, could show that respiratory training significantly reduces snoring. Persons with chronic bstructive pulmonary disease reported that they felt better after a respiratory training. D. Owassapian and Dr. T. Scherer are looking at these effects in an investigation at the Triemlispital, Zurich. Furthermore, M. Edelmann and Dr. C. Brunner study the effects of a respiratory training in para- and quadriplegics at the Paraplegikerzentrum, Nottwil. In summary, respiratory training alone can prolong exercise time during constant work exercise in both sedentary and active subjects. This observation suggests that the role of respiration during endurance exercise has been underestimated. It can even limit this type of exercise.